DESENVOLVIMENTO E CARACTERIZAÇÃO DE VESÍCULAS LIPOSSOMAIS CONTENDO TRIÓXIDO DE ANTIMÔNIO PRODUZIDAS VIA ASSISTÊNCIA DE ENERGIA ULTRASSÔNICA - Salles, Bruno do Canto (2019)
In the search of the balance between treatment efficiency and its less harmfulness in relation to human biological systems, the exploration by alternative therapeutic methods is becoming increasingly important. Making it necessary not only the search for mechanisms of action of drugs in front of the organism, but also a better efficiency of production, transport and activity of the same. Synthesis of liposomal vesicles with antimony trioxide by reverse phase evaporation method assisted by ultrasound emerges as an alternative to traditional methodologies for treating degenerative diseases and especially in acute myelocytic leukemia (AML) subtype FAB-M3 - promyelocytic leukemia acute (APL) - due to its easy obtainment and good biocompatibility. The objective of this dissertation was to develop and characterize antimony trioxide-containing liposomes with the aid of ultrasonic energy to reduce particle size and polydispersion index of the final liposomes. These liposomes were produced by the reverse phase evaporation method with ethyl acetate solvent. To evaluate the influence of ultrasound on the characteristics of liposomes, it was decided to use two probes with powers of 130 and 750W where the wave amplitude was tested from 30 to 60%. Methods with indirect sonication, high performance dispersion apparatus and magnetic stirring were also used to compare the final formulation characteristics. In the physicochemical characterization were evaluated pH, particle size and polydispersion index, active content (ICP-OES), encapsulation rate and stability. Being the stability study with the formulations being subjected to room temperature (25 ° C), refrigeration (4 to 8 ° C) and climatic chamber (40 ° C and 60% humidity), for a period of 90 days. The physicochemical characterization data showed that the best sonication condition was with 750 W power, 40% amplitude and 8 seconds ON and 2 seconds OFF cycles, to avoid heating and possible lipid degradation. The average size was 79.71 ± 1.07 nm and polydispersion index 0.222 ± 0.13 for white liposomes and 81.20 ± 1.18 nm and 0.271 ± 0.44 for liposomes containing antimony trioxide, respectively. The antimony trioxide content of the liposomes was 1.0 mg mL -1 and the encapsulation efficiency (% EE) 8.12 ± 0.72%. The stability study showed that the formulations remained stable for a period of 30 days in refrigerator and room temperature.